The Moderating Role of Education Level in the Relationship between Halal Labeling, Islamic Transactions, and Purchase Intentions - Lorena Dara Putri Karsono; Eva Tri Sakila (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Objective - This study examines the influence of halal labeling and Islamic transactions on purchasing intentions in platform Shopee Barokah on Generation Z in Kudus Regency, with education level as a moderating variable. Method- This study uses a causality method and a quantitative approach. The target population of this study is Generation Z in Kudus Regency. The research sample consisted of 100 respondents selected using a purposive sampling technique accidental sampling. The data source uses primary data in the form of a survey by providing questionnaires to be filled out by respondents. The data analysis technique usespartial least squares structural equation modeling (PLS SEM) with statistical tools onsoftware SmartPLS. Findings– Based on the research results, halal labeling and Islamic transactions significantly and positively influence consumer purchase intentions on Shopee Barokah. However, education level did not moderate the relationship between halal labeling and Islamic transactions and purchase intentions. Implications - This finding confirms the importance of halal labeling and Islamic transactions in encouraging purchasing interest in e-commerce Sharia, while education level does not act as a moderating variable in this context. This research provides important insights for developing digital marketing strategies based on Islamic values, particularly among Generation Z.